Cushion replacement in the second reinforcement bracing base course - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding cushion replacement in the second reinforcement bracing base course of BRAC University new campus project.